DILEMA ERA DIGITAL : DAMPAK POSITIF DAN NEGATIF MEDIA SOSIAL TERHADAP PROSES SOSIALISASI ANAK DI SDN NAMBO ILIR - Deayu Tania Putri; Desty Endrawati Subroto; Intan Fatimah; Novisah, Novisah (Sindoro: Cendikia Pendidikan, 2025)
Technology has become an integral part of everyday life,including in the field of education. Its presence-especially in the form of social media-offers numerous positive benefits but also brings potential negative impacts.In today’s digital era, social media is used by various groups, including elementary school students, as a means to interact and gain knowledge. Platforms such as YouTube, Google,and others have influenced how children communicate and socialize.This study aims to examine the impact of social media on the socialization of elementary school children,both in terms of its advantages and the challenges it poses.Additionally,the study seeks to identify strategies to optimize its benefits while minimizing its harmful effects. The research uses a descriptive qualitative method through a literature rivew,with data gathered from books,scientific journals,and other relevant sources.The findings indicate that social media significantly affects children’s patterns of communication and social interaction.While it offers advantages such as improving technological skills and social competence,it can also lead to negative effects like reduced face-to-face interaction and exposure to inappropriate content.Therefore,the active role of parents and educators is essential in providing proper supervision and guidance. Through these efforts,the negative impacts of social media on the socislization of elementary school children can be minimazed, while its positive effects can be maximized.